E-SERVICE QUALITY AND E–RECOVERY SERVICE QUALITY ON E–SATISFACTION LAZADA.COM - Hidayah, Riski Taufik; Utami, Eristy Minda (Fakultas Ekonomi, Universitas Negeri Jakarta, 2017)
The purpose of thus research is to find the impact of e-service quality and e – recovery service quality toward e-satisfaction of consumer at online marketplace Lazada. This research is triggered by the decreasing percentage of Top Brand Award on every category Lazada is in. Even though Lazada as an online service provider has done several effort to improve their service quality and respon to each complain in a well manner. The methods used in this research is descriptive and verificative. The population in this research are Lazada consumer whom conducted a complaint after they buy a product from Lazada. The sampling technique in this research is a purposive sampling, with the number of sample is 200 people. To analise the data the author used Path Analysis to understand the correlation wether it is simultaneous or partial.